Diferencias en las condiciones de vida de los comerciantes de productos agrícolas y no agrícolas del mercado mayorista del cantón Riobamba, provincia de Chimborazo, en el periodo 2024 - Yuquilema Manguia, Aron Israel (2024)
ABSTRACT: The main objective of this research is to analyze the differences in the living conditions of traders of agricultural and non-agricultural products in the wholesale market in Riobamba City, Chimborazo Province, in the period 2024. Information was collected through the living conditions instrument of the National Institute of Statistics and Census (INEC) households. For the development of the research, we used a mixed quantitative and qualitative approach with a nonexperimental design with a descriptive scope; also, for the sampling, we considered a finite population where we took into account the economic, housing, health, education and family dimensions; from each dimension we took the most important quantitative variable for the comparative analysis as monthly sales, number of medical checkups, number of times a week doing sports, meals a day, number of workshops attended per month, time spent with the family. Each of these variables underwent a statistical analysis between means and variances to then perform the contrast of hypotheses through the Man Whitney U test and find out which group is better. In qualitative variables such as type of housing, home ownership, level of education, family support in the business, and family support in difficult situations of life, a contingency table and chi-square test were performed to verify if there is a significant association. This test was also applied according to the level of sales of each group of traders to see if there was any statistically significant association in the living conditions. It is concluded that there are better living conditions for the agricultural traders in terms of monthly sales, medical assistance per year, and the number of times they do sports per week, while the non-agricultural trader receives more courses or workshops and estimates more time to spend with his family. The relationship of monthly sales between qualitative variables, for the most part, has a statistically significant association, making us understand that it directly affects the living conditions of the merchant.